Acidentes de trânsito em veículos de duas rodas: avaliação da gravidade das vítimas e lesões - Santos, Ana Carla Ferreira Silva dos (2013)
Traffic accidents have excelled with the growth of the number of victims involved with two-wheel vehicles which can cause serious injury and even death. This study aimed to correlate the victims of traffic accidents caused from high and low power two-wheeled vehicles, by means of determining the severity and injuries. This is a descriptive, cross-sectional, prospective study with a quantitative approach developed in the emergency service of a trauma reference public hospital in Sergipe state, Brazil during the months of August to December 2012. There were 321 interviews for two-wheeled vehicle accident victims, and 83 who used two-wheeled vehicles up to 100 horsepower (cc) and 229 above 100 cc. The average age of those victims was 32 years with a majority of males (88% and 93%), without licenses (88% and 73%) and previous involvement in accidents (52% and 55%) respectively. The most common trauma mechanism was slippage (25% and 31%), with a person on the vehicle at the time of the accident (62% and 69%), used for locomotion transportation (65% and 69%), without the use of a helmet (58% and 49%) and suspect of alcohol usage (48% and 35%) in the groups respectively. The determination of severity held by New Injury Severity Score (NISS) was greater in the head and neck regions and revealed the absence of association between the score NISS and the power of the vehicle (p=0.01), i.e. the severity of trauma on victims is independent of the vehicle having up to 100 cc (mopeds and scooters) or more than 100 cc (motorcycles). There was a statistically significant association between the NISS score and the number of regions affected (p=0.001) and regions most severely affected (p=0.002) for the group up to 100cc and above 100cc (p=0.001). It is concluded that the more severely affected victims which had a higher number of affected regions had greater severity and this was not related to the power of two-wheeled vehicles